Efecto antitumoral de los alcaloides hidrosolubles de Abuta grandifolía (MART) Satidwith, en Línea Celular HEP - 2 - Rojas V., Yeny (2004)
The ethanolic extract of the stalk of Abuta grandifolia(MART) Sandwith «abruta » contains two types of alkaloids, one is very soluble in ethilic ether one the other one is water soluble. They correspond to alkaloids of quaternary ammoniun type. They have citotaxic properties against formed system by eggs of sea urchin; and it confirmed against a VERO cell line.For determining the antitumoral effect, it was carried out an essay with cell line of the (HEP-2) human Laryngelal epydermoidal carcinoma resulting in a citotoxic response of 91% and 95% at a concentrations of 0.24 and 0.06 mg/dL.A alkaloid fraction named A, wich IR spectroscopical properties show absorption bands corresponding to alkaloids of quaternary ammonium type, it has antitumoral piopierties.